2017
DOI: 10.1159/000456619
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vitamin D on the Clinical Outcome of Gastro-Entero-Pancreatic Neuroendocrine Neoplasms: Report on a Series from a Single Institute

Abstract: Background/Aims: Vitamin D deficiency is hypothesized to represent a risk factor in several neoplasms. The aim of this study was to determine whether serum 25-hydroxyvitamin D (25-OHvitD) deficiency represents a risk factor for neuroendocrine neoplasms (NENs) and can be associated with overall survival (OS) and progression-free survival (PFS). Methods: From 2010 to 2015, 138 patients with gastro- entero-pancreatic NENs (61 females; median age, 63 years) were included in the study. Serum 25-OHvitD levels, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 47 publications
3
31
1
Order By: Relevance
“…In a recent study, Massironi et al found vitamin D deficiency in 33% and insufficiency in 68% of cases in an Italian population of 138 GEP-NET patients [22]. No differences in vitamin D levels were observed between pNET and other tumor sites, as well as no difference when considering tumor grades and staging [22]. Similarly, a more recent study by Robbins et al evaluating 183 patients with GEP-NET showed a prevalence of vitamin D deficiency/insufficiency in 63% of cases [30].…”
Section: Vitamin D In Gep-netmentioning
confidence: 94%
See 4 more Smart Citations
“…In a recent study, Massironi et al found vitamin D deficiency in 33% and insufficiency in 68% of cases in an Italian population of 138 GEP-NET patients [22]. No differences in vitamin D levels were observed between pNET and other tumor sites, as well as no difference when considering tumor grades and staging [22]. Similarly, a more recent study by Robbins et al evaluating 183 patients with GEP-NET showed a prevalence of vitamin D deficiency/insufficiency in 63% of cases [30].…”
Section: Vitamin D In Gep-netmentioning
confidence: 94%
“…The influence of medical treatment with SSAs on vitamin D levels is controversial. In the Italian study, it was highlighted that there were lower vitamin D levels in GEP-NET patients treated with SSAs compared to those not treated by SSAs [22]. On the contrary, the other two studies did not find any differences in vitamin D levels between NET patients with or without SSA treatment [29,30].…”
Section: Vitamin D In Gep-netmentioning
confidence: 96%
See 3 more Smart Citations